b+b+b+6=6b+5-2b+9

Simple and best practice solution for b+b+b+6=6b+5-2b+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b+b+b+6=6b+5-2b+9 equation:


Simplifying
b + b + b + 6 = 6b + 5 + -2b + 9

Reorder the terms:
6 + b + b + b = 6b + 5 + -2b + 9

Combine like terms: b + b = 2b
6 + 2b + b = 6b + 5 + -2b + 9

Combine like terms: 2b + b = 3b
6 + 3b = 6b + 5 + -2b + 9

Reorder the terms:
6 + 3b = 5 + 9 + 6b + -2b

Combine like terms: 5 + 9 = 14
6 + 3b = 14 + 6b + -2b

Combine like terms: 6b + -2b = 4b
6 + 3b = 14 + 4b

Solving
6 + 3b = 14 + 4b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-4b' to each side of the equation.
6 + 3b + -4b = 14 + 4b + -4b

Combine like terms: 3b + -4b = -1b
6 + -1b = 14 + 4b + -4b

Combine like terms: 4b + -4b = 0
6 + -1b = 14 + 0
6 + -1b = 14

Add '-6' to each side of the equation.
6 + -6 + -1b = 14 + -6

Combine like terms: 6 + -6 = 0
0 + -1b = 14 + -6
-1b = 14 + -6

Combine like terms: 14 + -6 = 8
-1b = 8

Divide each side by '-1'.
b = -8

Simplifying
b = -8

See similar equations:

| y^2+7y-30=0 | | 4x-2=-2x-56 | | 7x-10=-37-2x | | 8k-6+3k-2k+3=4*33 | | 6-5x-2x=34 | | 6w^2+33w-18= | | 2d-8-5d=-3d-2d+6 | | 15=3.4n-2(n-4) | | (3x)+(4x-24)=180 | | x^2+1045x+14278=0 | | P=100-0.5q | | 3c-6+2c=10c-2c+6 | | 5u+6v-3(3u-2v)= | | 2n-4m=8 | | 12s^2-13st-4t^2= | | 15x-10=-9x+12 | | 10x+1=2x+5 | | 41-8x=-6x-23, | | 3(3x+4)-2-5-7x=20 | | -7q+8-6+5q=8 | | 3x+16=12x-74 | | -r+7r-3+5r=93 | | w=mt+b | | =2(3s-8)+7 | | -(4x-4)-(-2x-6)+3=-3(x-1)-(6x+2)+3 | | 2b-10b-15+5=8b-40-4b-6 | | 10x^4-21x^2+9= | | 6a+3a=18 | | 3x+14+2x+1=180 | | 11a-4a-18=2a+a+10 | | 9x-5x-x=9 | | 9x-5x-x=19 |

Equations solver categories